The relationship between interleukin-6 and functional connectivity in methamphetamine users. (11th June 2018) - Kohno, Milky; Loftis, Jennifer M.; Huckans, Marilyn; Dennis, Laura E.; McCready, Holly; Hoffman, William F.
Highlights: Interleukin 6 (IL-6) levels are higher in methamphetamine (MA) users than in controls. Relationships between functional connectivity (FC) and IL-6 differ by group. Striatolimbic FC and IL-6: positively related in MA users but negatively in controls. Corticostriatal FC and IL-6: unrelated in controls and negatively related in MA users. Abstract: Methamphetamine (MA) causes an increase in pro-inflammatory cytokines in animal models and in humans. Resulting activation of microglia and neuro-inflammation could, via effects on reward networks, mediate behavioral characteristics of addiction. We examined the relationship between interleukin-6 (IL-6) and corticolimbic and striatolimbic resting-state functional connectivity (RSFC). Thirty adults diagnosed with MA dependence and 20 control subjects underwent a resting-state functional magnetic resonance imaging (fMRI) scan and gave a blood sample for determination of plasma IL-6 levels. Seed-based RSFC analyses were performed to examine the interactive effect of group and IL-6 on ventral striatal and prefrontal connectivity. Within the MA group, IL-6 levels were positively related to striatolimbic RSFC but negatively related to corticostriatal RSFC. Our findings with IL-6 support the idea that inflammation may at least partly mediate the link among MA use disorder, RSFC, and behavior, possibly via effects on mesolimbic and mesocortical dopaminergic systems.